Academic and clinical integrity: undergraduate nursing students’ perceptions - Faisa Farah (22457698) (2025)
Background Despite education on academic integrity, there are still instances where nursing students breach academic integrity principles. Nursing students who breach academic integrity principles in the classroom might engage in dishonest behaviors in the clinical setting. Globally, there are limited studies on nursing students’ perceptions of academic and clinical integrity. Furthermore, there are no studies on the perceptions of nursing students in Qatar on academic and clinical integrity. Purpose To explore the perceptions of undergraduate nursing students in Qatar on academic and clinical integrity. Methods A descriptive qualitative inquiry using face-face and online interviews. Results Four major themes and sub-themes emerged: (1) Definitions of Academic and Clinical Integrity; (2) Facilitators of Academic and Clinical Integrity with sub-themes of institutional support, ethical practice, and professional practice; (3) Barriers to Academic and Clinical Practice with sub-themes of peer influence, time influence, and fear of mistakes; (4) Improvements to academic and clinical integrity at the institutional level. Conclusion Participants in this study viewed academic and clinical integrity from a positive lens. Identified facilitators and barriers to academic and clinical integrity from a nursing student perspective in Qatar align with global nursing student perspectives. Other Information Published in: International Journal for Educational Integrity License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s40979-025-00188-5